Complexation of some trivalent lanthanides, scandium(III) and thorium(IV) by benzylidenepyruvates in aqueous solution - Marques, R. N. [UNESP]; Melios, C. B. [UNESP]; Pereira, N. C. S. [UNESP]; Siqueira, O. S.; De Moraes, M. [UNESP]; Molina, M.; Ionashiro, M. [UNESP] (Elsevier, 1997)
The protonation constants of 4-methylbenzylidenepyruvate (4Me-BP) and 4-isopropylbenzylidenepyruvate (4IP-BP) as well as the stability constants of their binary 1:1 complexes with Cu(II), La(III), Pr(III), Sm(III), Eu(III), Yb(III), Sc(III) and Th(IV) have been determined spectrophotometrically in aqueous solution at 25°C and ionic strength 0.500 M, maintained with sodium perchlorate. For all metal ions considered, the stability changes move in the same direction as the pKa of the ligands. Linear free energy relationships, as applied to oxygen donor substances, suggest the -COCOO- moiety as the metal binding site of the ligands. The results are discussed mainly taking into account that benzylidenepyruvates, besides the α-keto canonical form, may display other forms in aqueous solution with changing pH and the possible occurrence of extra intra-ligand charge polarization, induced by metal ions.
Keywords: Benzylidenepyruvates; Metal-ion complexes; Protonation